Analysis on the fitness of heat-resistant steel as casing material in corrosive environment at high temperature. (January 2023) - Fan, Zijian; Zhong, Xiankang; Yao, Jinxing; Zhang, Zhixin; Hu, Junying
Highlights: Study of extreme condition has great significance to deep oil and gas exploitation. An overall analysis of steel from mechanical properties and corrosion resistance. Heat-resistant steel shows good resistance of SCC at high temperatures. Abstract: This study investigates the performance of heat-resistant steel in a corrosive environment at high temperatures, focusing on mechanical characteristics and corrosion behavior. Firstly, the performance of heat-resistant steel at high temperature was verified using mechanical property measurement, fracture failure analysis, and high-temperature creep test. The results indicate that the tensile strength and yield strength of heat-resistant steel at 350 °C are separately for 930 MPa and 776 MPa. The specimen has good creep resistance and no creep between 100 ∼ 350 °C. After establishing that the high-temperature performance of heat-resistant steel complies with the specifications, the weight loss and stress corrosion tests were carried out in a corrosive environment at high temperatures. The results reveal that the corrosion rate is 0.9504 mm/a at 350 °C, and the corrosion products mainly consist of FeSx, FeCO3 and Fe3 O4 . The four-point bending test specimen did not crack at all test temperatures. The results show that heat-resistant steel has excellent properties and can be used as the casing material of a complex deep well at high temperatures.